Análise discursiva dos comentários postados na ferramenta fórum da disciplina leitura e produção textual no espaço Unisul/Virtual de aprendizagem - Silva, Simone Atayde Floriano da (2010)
This thesis presents the results of a survey which aimed to review the comments posted in Space UnisulVirtual Learning (EVA), more specifically the tool UnisulVirtual Forum, the discipline of reading and writing – 2008/2. Our objectives in this investigation were to analyze the functioning of the speeches that materialize in this space and the characteristics of expository speeches. Evidence, too, which are the subjects who set out to tell and the discursive conditions of its production based on the theories devised by scholars of discourse analysis of current French. Divided into three chapters, our first paper highlights the conceptual formulations, such as language (gem) in / for discourse analysis, basic conditions of production, discourse, interpretation, ideology, discursive formation, according to inter; heterogeneity (s) enunciative (s) to finish with the discursive ethos and the scene of enunciation, in the light of the theoretical Pêcheux; Authier-Revuz, Orlandi; Maingueneau. Thus, the theoretical starting point of the analysis is based on the formulation of Orlandi (2003) which proposes the creation of pedagogic discourse (DP), predominantly in the authoritative discourse. However, the fact that the tool Forum participants work in the midst by multiple interactive processes enabled us to think that there is a slip with reference to the pedagogic discourse (monophonic and narrow sense), which produces an operation of DP less focused on authoritative discourse, and encourage the introduction of controversial speech. In the second chapter, we present the research context and presents the analysis devices. And the third chapter in the discursive practices identified in academic subject-DP in the characteristics of the media space, which underlies the controversial speech – polysemy arises when the subject arises in the interaction of quotas for blacks in universities - which allows participants to open to diverse locations. In this case, the analysis turned to understanding the relationship subjectivity/subject/discourse that allowed us to see how the guy in the toolacademic forum is composed of several others. Thus, the production and circulation of discourse in the Forum indicate that knowledge is not taken as "product" but as "process" in which the students themselves manage knowledge